Cholestasis-associated reproductive toxicity in male and female rats: The fundamental role of mitochondrial impairment and oxidative stress. (November 2019) - Ommati, Mohammad Mehdi; Farshad, Omid; Niknahad, Hossein; Arabnezhad, Mohammad Reza; Azarpira, Negar; Mohammadi, Hamid Reza; Haghnegahdar, Maral; Mousavi, Khadijeh; Akrami, Shiva; Jamshidzadeh, Akram; Heidari, Reza
Graphical abstract: Cholestasis and accumulation of cytotoxic molecules (e.g., hydrophobic bile acids) are connected to a wide range of organ injury. Reproductive organs in both males and females could be affected by cholestasis. The data collected in the current study represent severe oxidative stress and mitochondrial impairment as fundamental mechanisms of cholestasis-associated reproductive toxicity. Highlights: Cholestasis and accumulation of cytotoxic molecules ( e.g., hydrophobic bile acids) affects several organs. The reproductive system could be affected by several diseases as well as toxic insults. We found that cholestasis significantly affected the reproductive system in both male and female cholestatic animals. Oxidative stress and mitochondrial impairment play a primary role in cholestasis-associated reproductive toxicity in males and females. Abstract: Cholestasis is a significant decrease in bile flow. The liver is the primary organ affected by cholestasis. Chronic cholestasis could entail to tissue fibrotic changes and liver cirrhosis. Other organs, including heart, kidneys, nervous system, skeletal muscles, as well as the reproductive system, might also be affected during cholestasis. Although the cholestasis-associated pathological and biochemical alterations in organs such as liver have been widely investigated, there is little information about complications such as cholestasis-induced reproductive toxicity. The current study aimed to evaluate the pathologic effects of cholestasis on reproductive organs in both male and female animals. Rats underwent bile duct ligation (BDL) surgery. Markers of reproductive toxicity, including serum hormonal changes, tissue histopathological alterations, biomarkers of oxidative stress, and markers of mitochondrial impairment, were evaluated. Increased serum markers of liver injury and elevated level of cytotoxic molecules such as bile acids and bilirubin were evident in BDL animals. On the other hand, the serum level of hormones such as testosterone was suppressed in BDL rats. Significant histopathological alterations were also evident in the testis and ovary of BDL animals. A significant increase in oxidative stress markers, including ROS formation, lipid peroxidation, protein carbonylation, and depleted glutathione and antioxidant reservoirs were also detected in BDL rats. Moreover, mitochondrial depolarization decreased dehydrogenases activity, and depleted ATP content was detected in sperm isolated from the BDL group. These data indicate that cholestasis-associated reproductive toxicity in male and female rats is restrictedly coupled with severe oxidative stress and mitochondrial impairment.